Context, visibility, and control: Police work and the contested objectivity of bystander video. (January 2019) - Newell, Bryce Clayton
This article examines how police officers understand and perceive the impact of bystander video on their work. Drawing from primarily qualitative data collected within two police departments in the Pacific Northwest, I describe how officers' concerns about objectivity, documentation, and transparency all manifest as parts of a broader politics of information within policing that has been amplified in recent years by the affordances of new media platforms and increasingly affordable surveillance-enabling technologies. Officers' primary concerns stem from their perceived inability to control the context of what is recorded, edited, and disseminated to broad audiences online through popular platforms such asYouTube.com, as well as the unwanted visibility (and accountability) that such online dissemination generates. I argue that understanding the effects of this `new visibility' on policing, and the role played by new media in this process, has become vitally important to our tasks of organizing, understanding, and overseeing the police.